Scientific reconstruction of local plants as the basic materials of Batik Natural Dyes. (March 2020) - Tresnawati, N; Saleh, I; Sudarmin,; Wardani, S
Abstract: The Ciwaringin batik has different features compared to other Cirebon Batik Tulis. It has a unique motif and soft batik color produced from natural dyes. This research aims to reconstruct the knowledge of the community in using local plants as basic material of natural dyes at Ciwaringin, Cirebon, becomes a scientific knowledge. This research was qualitative descriptive research. Data were collected through observation, in-depth interviews, discussion with batik artisans, documentation, and literature study. Data were analyzed by using verification, reconstruction, formulation, conceptualization, and documentation, to obtain scientific knowledge. The subject of this research is the batik artisans of Ciwaringin batik. The result showed that Indigenous knowledge to utilize the local plant as a natural dye of batik by Ciwaringin community is unique local wisdom to maintain environmental balance. Their scientific concepts that have been identified and documented systematically are scientific knowledge that has not been yet formalized. The cause and effect relationship was known through a verification process and then were reconstructed and conceptualized into formal scientific knowledge. The scientific knowledge can be used as a source of culture-based science learning in schools called ethnoscience. The implications of this research are environmental conservation and the increasing value of local wisdom.